Production of [xi][star] resonances in [sigma]- induced reactions at 345 GeV/c - Adamovič, M. I.; Siebert, Hans-Wolfgang (The European physical journal. C, Particles and fields, 1999)
We report on a measurement of the differential and total cross sections of inclusive production of Ξ∗Ξ∗Ξ^* resonances in Σ−Σ−Σ^--nucleus collisions at 345 GeV/c. The cross section for inclusive Ξ01530Ξ15300Ξ^0_{1530} production is about a factor of 5 below that of Ξ−1320Ξ1320−Ξ^-_{1320} hyperons. The products of cross section and branching ratio for the observed channels Ξ01690→Ξ−π+Ξ−1820→Ξ01530π−Ξ16900→Ξ−π+Ξ1820−→Ξ15300π−Ξ^0_{1690} → Ξ^- π^+ Ξ^-_{1820} → Ξ^0_{1530} π^- and Ξ−1950→Ξ01530π−Ξ1950−→Ξ15300π−Ξ^-_{1950} → Ξ^0_{1530} π^- are lower by yet another order of magnitude. The Ξ−1820Ξ1820−Ξ^-_{1820} and Ξ−1950Ξ1950−Ξ^-_{1950} resonances show significantly harder xFxFx_F and ptptp_t distributions than Ξ−Ξ−Ξ^- and Ξ01530Ξ15300Ξ^0_{1530} hyperons. A comparison of the xFxFx_F-distribution to PYTHIA and QGSM predictions provides only a partial agreement.
Im Titel werden Xi, Star und Sigma als griechische Buchstaben dargestellt
Im Titel ist das Minuszeichen nach Sigma hochgestellt
Gesehen am 27.02.2020